ISLAMIC RELIGIOUS EDUCATION TEACHER STRATEGY IN MULTICULTURAL - BASED STUDENT BEHAVIOR DEVELOPMENT - Rahmat Muliana (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2024)
Religious education is a combination of basic knowledge that occurs in a person's personality. So that teachers cannot utilize multicultural values ​​​​to shape students' personalities. This study aims to define the strategies and implications of Islamic education. Islamic education basically aims to foster multicultural student behavior. To answer this problem, this study is a qualitative study with the aim of understanding primary data sources including principals, painters, and students, as well as secondary data sources including archives on the implementation of multicultural-based Islamic Religious Education activities. This study uses data analysis techniques through data education, data presentation, data verification, and drawing conclusions. This study is that the strategy of Islamic Religious Education teachers in fostering multicultural-based student behavior in Lombok State Elementary Schools is to view and place all students equally and integrated with multicultural values ​​​​in Islamic Religious Education learning, such as: having values ​​​​of respecting differences, being fair, honest, responsible, honest in trust, self-confidence, cooperation, and deliberation.